Analisis Komprehensif Instrumen Moneter Syariah: Sukuk, PUAS, dan Repo Syariah untuk Stabilitas Keuangan Islam di Indonesia - Annisyah Nur Silalahi; Dita Handayani; Faris Haikal Hasibuan; Reni Ria Armayani Hasibuan (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
This research offers an in-depth examination of three primary Sharia monetary tools—Sukuk, the Sharia Interbank Money Market (PUAS), and Sharia Repo—aimed at enhancing the resilience of Islamic financial systems in Indonesia. Through a descriptive review of existing literature, the paper details Sukuk as asset-supported securities for medium- to long-term funding, PUAS operations grounded in mudharabah and wakalah agreements for brief interbank dealings, and Sharia Repo via SBSN sell-and-buyback arrangements to streamline Sharia bank liquidity. Results indicate these tools work in tandem to handle surplus funds, curb inflation, and bolster Bank Indonesia's monetary framework absent any speculative practices. Policy recommendations emphasize advancing education efforts, regulatory innovations, and infrastructural upgrades to promote equitable expansion within Sharia finance.